2013
DOI: 10.3109/02699052.2013.767938
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated sessions of galvanic vestibular stimulation on target cancellation in visuo-spatial neglect: Preliminary evidence from two cases

Abstract: Results: Analyses of variance indicated that both participants missed significantly fewer targets in both tasks on the fifth day of stimulation compared to baseline. More so, this improvement was still evident at follow-up three days later. Conclusion:The results strengthen the need for a larger, sham-controlled trial to establish whether repeated GVS provides lasting relief from neglect.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…These studies suggest that repeated administration not only increases the length of recovery, but also the magnitude of recovery. Contrary to the preliminary data described above (Kerkhoff et al, 2011; Schmidt et al, 2013; Zubko et al, 2013), these studies imply that GVS may be most effective when repeatedly, as opposed to singularly, applied.…”
Section: Introductioncontrasting
confidence: 79%
See 3 more Smart Citations
“…These studies suggest that repeated administration not only increases the length of recovery, but also the magnitude of recovery. Contrary to the preliminary data described above (Kerkhoff et al, 2011; Schmidt et al, 2013; Zubko et al, 2013), these studies imply that GVS may be most effective when repeatedly, as opposed to singularly, applied.…”
Section: Introductioncontrasting
confidence: 79%
“…However, as mentioned in the Introduction, three, small GVS studies have shown carry-over from a single session (Kerkhoff et al, 2011; Schmidt et al, 2013; Zubko et al, 2013). This may partly stem from the fact that the vestibular nerve is stimulated many thousands of times during a single 25–30 min session.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wilkinson and colleagues have also found that noisy GVS can attenuate prosopagnosia (Wilkinson et al, 2005) and figure copying deficits (Wilkinson et al, 2010). In the most recent study involving two patients with visuo-spatial neglect, GVS was found to have a lasting beneficial effect in a target cancellation task (Zubko et al, 2013). In one of the most systematic studies to date, Dilda et al (2012) found that suprathreshold GVS significantly increased the error rates for match-to-sample and perspective-taking tasks compared to a subthreshold GVS group; however, reaction time, dual tasking, mental rotation and manual tracking were not significantly affected.…”
Section: Effects Of Artificial Vestibular Activation On Memory In Humansmentioning
confidence: 99%